2006
DOI: 10.1080/08035250600724507
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal growth, neurodevelopment and altered adiposity after preterm birth—from a clinical nutrition perspective

Abstract: Optimal nutritional management to minimize hyperinsulinaemia and insulin resistance may potentially improve neurodevelopment and facilitate catch-up growth with normal body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 66 publications
1
71
1
1
Order By: Relevance
“…It has been shown that impaired weight gain, especially among infants born small for gestational age, is associated, in the short-term, with infant mortality and morbidity 25 and, in the long-term, with suboptimal neurological development, 26 short stature, 27 coronary heart disease 28 and stroke. 29 Undernutrition in infancy, in particular in the second half of the first year of life, is the underlying cause of most infant mortality in low-income countries and the vicious cycle between malnutrition and infections is a frequent occurrence.…”
Section: Statement Of Purpose and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that impaired weight gain, especially among infants born small for gestational age, is associated, in the short-term, with infant mortality and morbidity 25 and, in the long-term, with suboptimal neurological development, 26 short stature, 27 coronary heart disease 28 and stroke. 29 Undernutrition in infancy, in particular in the second half of the first year of life, is the underlying cause of most infant mortality in low-income countries and the vicious cycle between malnutrition and infections is a frequent occurrence.…”
Section: Statement Of Purpose and Methodsmentioning
confidence: 99%
“…During catch-up growth, an infant below the expected weight for gestational age at birth gains weight rapidly to reach a weight corresponding to his/her genetic potential. Because catch-up growth represents a normalization of a previously abnormal growth pattern and because it is associated with improved neurological development 26 and other benefits, 25 catch-up growth is generally seen as a desirable growth pattern. However, in the specific context of rapid weight gain as a predictor of later obesity, it is unclear if infants who experience catch-up growth after intrauterine growth retardation are protected against an increased risk of obesity or if rapid weight gain, even in the context of catchup growth, is just a particular case of rapid weight gain associated with later development of obesity.…”
Section: Statement Of Purpose and Methodsmentioning
confidence: 99%
“…In preterm infants, concern about rapid postnatal growth, fat accumulation, and their potential adverse effects has increased interest in the composition and proportionality of postnatal growth. [5][6][7][8][9][10][11][12] Because there is no routine clinical measurement of body composition in the NICU setting, a proxy such as BMI could be a useful clinical tool for preterm infants.…”
mentioning
confidence: 99%
“…Once EUGR occurs, excessive catch up growth may lead to increased adiposity and insulin resistance and metabolic syndrome later in life (Yeung 2006, Morrison et al 2010). This has led to a dilemma after discharge: whether to aim for better nutrition to achieve improved neurodevelopmental outcomes, which may come at a cost of early-onset obesity and diabetes (Ong 2007).…”
Section: Introductionmentioning
confidence: 99%